A CORPUS-BASED ANALYSIS OF NEOLOGISMS FROM ENGLISH INTO UZBEK IN SOCIAL MEDIA AND ONLINE CORPORA - Polvannazirova, Sevara (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article investigates the phenomenon of lexical innovation in Uzbek, focusing on borrowings from English and their integration into the Uzbek lexicon through social media and online communication. Utilizing a corpus-based approach, the study analyzes large-scale datasets derived from digital platforms, including social media networks, news websites, and online forums, to track the emergence and dissemination of neologisms. The findings reveal a significant prevalence of English borrowings in domains such as technology, business, and culture, which are adapted into Uzbek through phonological adaptation, semantic extension, and morphological modification. The study highlights the role of digital communication as a catalyst for linguistic change, facilitating the rapid spread and normalization of new lexical items. These insights contribute to a deeper understanding of language contact and lexical evolution in the digital age, raising important questions about language preservation and cultural identity. The article concludes with implications for future research, emphasizing the need for further exploration of corpus-based methodologies and the long-term impact of digital communication on language dynamics.